Low Phylogenetic Beta Diversity and Geographic Neo‐endemism in Amazonian White‐sand Forests. (18th January 2016) - Guevara, Juan Ernesto; Damasco, Gabriel; Baraloto, Christopher; Fine, Paul V. A.; Peñuela, María Cristina; Castilho, Carolina; Vincentini, Alberto; Cárdenas, Dairón; Wittmann, Florian; Targhetta, Natalia; Phillips, Oliver; Stropp, Juliana; et al.
Abstract: Over the past three decades, many small‐scale floristic studies of white‐sand forests across the Amazon basin have been published. Nonetheless, a basin‐wide description of both taxonomic and phylogenetic alpha and beta diversity at regional scales has never been achieved. We present a complete floristic analysis of white‐sand forests across the Amazon basin including both taxonomic and phylogenetic diversity. We found strong regional differences in the signal of phylogenetic community structure with both overall and regional Net Relatedness Index and Nearest Taxon Index values found to be significantly positive leading to a pattern of phylogenetic clustering. Additionally, we found high taxonomic dissimilarity but low phylogenetic dissimilarity in pairwise community comparisons. These results suggest that recent diversification has played an important role in the assembly of white‐sand forests causing geographic neo‐endemism patterns at the regional scale.